“Diseño de planta de tratamiento de aguas residuales para el campus La María de la Universidad Técnica Estatal de Quevedo” - Ibarra Gamboa, Dennise Liseth (2020)
The present investigation had the purpose of designing a wastewater treatment plant for the La María campus of the Quevedo State Technical University (UTEQ). The geometric method was applied to obtain the projection of the future student population in 10 years, which allowed the estimation of the average (9.30 l/s), maximum (18.60 l/s) and minimum (4.65 l/s) flows of wastewater production, according to the guidelines of the INEN 1108 Standard. On the other hand, the most suitable wastewater treatment technology was selected by applying the AHP and TOPSIS multicriteria analysis methods, the results of which determined that the best alternative for biological wastewater treatment is the extended aeration activated sludge process. Finally, the proposed scheme for the wastewater treatment plant at the La María campus includes the design of the screening unit, a sand trap, a flow equalization tank, an extended aeration activated sludge process (two-chamber bioreactor plus a secondary clarifier) and sludge dewatering by means of drying beds. Key words: Wastewater treatment, pollution, downloads, alternatives, water quality